Science‐policy interfacing on the issue of groundwater and groundwater‐dependent ecosystems in Europe: implications for research and policy. (20th August 2014) - Batubara, Bosman; Batelaan, Okke; Quevauviller, Philippe
Abstract : A policy‐oriented research initiative should be directed to support the development of environmental policy, tackling specific questions and identifying policy gaps. However, that is not always the case. Recent research designed to assist in the revision of the European Union's (EU's) Groundwater Directive (GWD) illustrates different interpretations of research needs by scientists. The EU's GWD made a specific call for research to provide better criteria for ensuring groundwater ecosystem quality and protection (recital 20 of the directive). To date, scientific responses actually focused on a better understanding of groundwater‐dependent (aquatic and terrestrial) ecosystems which contributed to a better approach of environmental quality standards (threshold values) but did not fulfil the specific request of the Directive. In term of policy, on‐going research is aiming at contributing to the revision of the GWD regarding chemical aspects (and better knowledge of groundwater interactions with associated ecosystems) but is not addressing specific groundwater ecological aspects as required in the Directive's recital. Looking ahead, a stronger interface between policy makers and scientists in the EU is necessary to ensure that research better addresses specific requests of the GWD. WIREs Water 2014, 1:561–571. doi: 10.1002/wat2.1041 This article is categorized under: Water and Life > Nature of Freshwater Ecosystems Human Water > Water Governance Science of Water > Water Quality